Review of Postpartum Contraceptive Practices at Chiang Mai University Hospital: Implications for Improving Quality of Service - Chaovisitsaree S. (2014)
Objective: To evaluate the acceptance rate and patterns of contraceptive use among postpartum women. Subjects and Methods:The records of 1,009 postpartum women attending the Family Planning Clinic at Chiang Mai University Hospital, Thailand, during January to December 2009 were reviewed. Results: Mean age was 28.2 ± 5.7 years (range 15-48). Almost all 920 women (91.2%) practiced breastfeeding. The acceptance rate of contraception was 97.6%. The types of contraceptive used were: depot medroxyprogesterone acetate, 387 (38.4%); progestin-only pills, 262 (26.0%); tubal resection, 201 (19.9%); male condom, 78 (7.7%); oral combined pills, 49 (4.9%); intrauterine device, 5 (0.5%); implant, 3 (0.3%). Among women undergoing tubal resection, 29 (14.4%) were ≤24 years of age. Significant independent predictors for using long-acting reversible contraception were young age and little or no formal education. Conclusion:The acceptance rate of contraception in this study was high. However, the following issues need to be evaluated: compliance of women using progestin-only pills, awareness of long-acting reversible contraception as an alternative option in women considering sterilization, and interventions to promote the use of intrauterine devices and implants. Copyright © 2011 S. Karger AG, Basel.